PENGARUH QUENCHING DAN TEMPERING PADA BAJA JIS GRADE S45C TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO CRANKSHAFT - Handoyo, Yopi (JURNAL ILMIAH TEKNIK MESIN, 2015)
Investigations have been conducted on JIS S45C steel the results of Quenching and Tempering. Process ofQuenching is conducted in 880ºC with holding time 50 minutes, with cooling medias quench of oil and water,continue proses of Tempering is conducted in 560ºC with holding time 40 minutes. Testing conducted : Thechemical composition testing, macro strucktur testing, hardness testing, and metallografth testing.The chemicalcomposition testing shows that steel S45C in the medium carbon steel with the content carbon 0,45%. Thespeciment non heat treatment, average result of hardness section upper is 19,2 and section lower is 18,8HRcand micro struckur is pearlite and ferrite. The speciment heat treatment in 880ºC with quenching media of oil,average result of hardness section upper is 35,3 dan section lower is 31,6HRc and micro struktur is bainite andmartensite. The speciment with heat treatment in 880ºC with quenching media of water, average result ofhardness section upper is 43,5 dan section lower is 37,5HRc and micro struktur is bainite and martensitedominant. The speciment with heat treatment in 880ºC quenching media of oil and continue Tempering in 560ºCcooling media of water average result of hardness section upper is 26,8 dan section lower is 23,3HRc and microstruktur is bainite and martensite. The speciment with heat treatment in 880ºC quenching media of water andcontinue Tempering in 560ºC cooling media of water, average result of hardness section upper is 27,8 dansection lower is 26,6HRc, and micro struktur is bainite and martensite smooth.Key words: quenching, tempering, JIS S45C steel.